Analysis of the epidemiological profile of patients treated at the dermatology outpatient clinic of a public hospital in the central region of Rio Grande do Sul - Marchi, Maria Clara Clara Chaves; Benetti, Romano Bortoluzzi; Timm Marques, Clandio; Filipin Rangel, Rosiane; Pizarro Meneghello, Luana (Disciplinarum Scientia | Saúde, 2024)
Skin diseases are influenced by different factors, allowing the association of the prevalence of certain dermatological pathologies with the epidemiological profile of the patients. This is an observational, retrospective, and descriptive study, with analysis of medical records and care forms, in a Dermatology outpatient clinic of a medium-sized hospital, located in the central region of the state of Rio Grande do Sul. The data refer to the period from January 2020 to December 2022. From the sample of 264 patients, 173 (65.5%) were female, and 91 (34.5%) were male. Regarding the most prevalent diagnoses in the consultations, 16 (6.1%) corresponded to seborrheic keratosis, followed by 15 (5.7%) of acne and actinic keratosis and 12 (4.5%) of psoriasis. There is a possibility of demand bias because this is a low-complexity outpatient clinic, i.e., more serious cases, especially those with suspected malignant skin neoplasms, may be referred to another high-complexity referral center in the city. The analysis of the epidemiological profile of this study allowed us to conclude that the patients seen at the outpatient clinic are mostly women, have a mean age of 45 years, come from all regions of the city, and have systemic arterial hypertension as their main comorbidity.